Pendampingan Guru Sains SD Melalui Pelatihan Pembuatan Media Pop-up Book Untuk Meningkatkan Literasi Baca Tulis. - Andari Puji Astuti; Venissa Dian Mawarsari; Martyana Prihaswati (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
The demands of the development are increasingly advanced with the era of the industrial revolution 4.0, of course, requires teachers to be proficient in mastering teacher competencies, not least in the use of learning media. But in the learning process there is still a lack of learning media. In addition to the implementation of the 2013 curriculum, teachers are still limited in the preparation of administration and learning devices only. In the implementation of the learning process there are still many teachers who use the expository learning model. This is due to the low level of knowledge of SD Negeri Meteseh teachers in making innovations and learning media that implement scientific approaches. The low knowledge of teachers about learning media innovations has the effect of less motivated students in the learning process, especially 3-dimensional learning media. For this reason, the proposing team provided a solution in solving these problems, namely by planning a training program for the teachers of SD Negeri Meteseh in making Learning Media. Learning media in the form of Pop Up Book for elementary school teachers. The result of this activity is that most teachers have never received pop up book learning media training. The teachers gave a positive response to the activities carried out. Teacher creativity in making learning media in the form of pop-up books increases. With the pop-up book the teacher can provide real concepts in the form of 3D images to students at the elementary level. In addition, basic literacy especially in reading skills of elementary students also increases..